Otimização da reação de knoevenagel em sistema binário etanol:água - Ferreira, João Marcos Gomes de Oliveira (2016)
In the current scientific scenario is increasing the need for new methodologies that meet both their main goal, which was developed as the expectations of a green chemistry, concerned about the environment and reducing impacts on it. Faced with such a need to adapt, have been developing alternative means to provide it. Recyclable catalysts; exchange of substrates; use of less toxic reagents; reactions without catalysts and/or free of solvents, are being proposed and boasting good results to your goals. Glimpsing a new reaction system for the Knoevenagel condensation, was developed a system without catalyst in a standard reaction between benzaldehyde and malononitrile, in order to meet your requirements best, and their conditions of operation. Among the tests of the solvent, which most outstanding in terms of increased speed of reaction by incidence of the solvent effect was a binary mixture of ethanol: water (3:7). It was apparent the need for heating, showing better reaction time in the range of 75-80° C, and 0,4 mL of binary mixture for each mole of substrates. Seen such conditions, the system was applied to a series of compounds with active methylene, aldehydes and ketones, in order to understand its Among the tests, the system has proven feasible to use malononitrile, cyanoesters, Meldrum's acid and Indandione with active methylene compounds as the Knoevenagel condensation; Malonitrile being the most reactive. The binary mixture was effectively applied in the Knoevenagel condensation reaction to a variety of structurally different aldehydes, where we observed a quick conversion with products of the 60 min to 1 min of time reactional and satisfactory income of 55 to 100%. For aliphatic ketones, the optimized system afforded reaction times of 5 to 6 hours, with satisfactory yields 74-75%.